2010
DOI: 10.4141/cjas09078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine on whole body and splanchnic energy metabolism in Holstein steers

Abstract: . 2010. Effect of ractopamine on whole body and splanchnic energy metabolism in Holstein steers. Can. J. Anim. Sci. 90: 77Á85. This study was designed to examine the influence of ractopamine (RAC) on whole-body and splanchnic energy balance. Six growing Holstein steers [body weight (BW) 0402939.5 kg] surgically fitted with an arterial and portal, hepatic, and mesenteric venous indwelling catheters were used in a repeated measures study. Treatments were a basal diet of alfalfa cubes fed at approximately1.5 ) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the present study, urine output was lesser in steers receiving ractopamine HCl, contributing to the lesser overall N excretion by ractopamine HCl-fed steers. It is unclear if others have noted similar effects of ractopamine HCl supplementation, as no studies completed with cattle supplemented ractopamine HCl report total urine output (Abney et al, 2007;Walker et al, 2007;Koontz et al, 2010). However, research in swine suggests a decrease in urine output can occur with ractopamine HCl supplementation (Ross et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, urine output was lesser in steers receiving ractopamine HCl, contributing to the lesser overall N excretion by ractopamine HCl-fed steers. It is unclear if others have noted similar effects of ractopamine HCl supplementation, as no studies completed with cattle supplemented ractopamine HCl report total urine output (Abney et al, 2007;Walker et al, 2007;Koontz et al, 2010). However, research in swine suggests a decrease in urine output can occur with ractopamine HCl supplementation (Ross et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Steers were fed treatments for 7 d in individual pens before being transferred to metabolism stalls (1.52 m × 2.13 m) for the measurement of respiratory gas exchange using indirect calorimetry. The design of the head-box-style respiration chambers was previously described by Koontz, et al [29]. Each respiration chamber was fitted with a waterer, feeder, and air-conditioning unit to maintain consistent temperature (21 • C) and relative humidity (35%).…”
Section: Respiratory Gas Exchangementioning
confidence: 99%
“…The observed improvement in feed efficiency (G:F) with RAC supplementation was likely because of its function as a repartitioning agent ( Moloney et al, 1991 ). Koontz et al (2010) found that RAC does not change whole-body energy balance yet reduces splanchnic energy use, and therefore increases energy availability for use by peripheral tissues. The reductions in KPH and marbling score and increases in LMA in this study are carcass indicators for effects of repartitioning of energy from adipose tissue by RAC.…”
Section: Discussionmentioning
confidence: 92%